The Implementation of Making Land Deed Done by Subdistrict Head as The Temporary Land Deed Officials in Bulakamba Subdistrict, Brebes Regency - Opy Ropiyah; Kholid Mawardi; Munsharif Abdul Chalim (Jurnal Akta, 2018)
The implementation of Land Registration Services by the Subdistrict Head as Temporary PPAT is referred to PP No 24 year 1997 on land registration, and PP No. 24 year 2016 concerning Land Deed Officials.The purpose of this study was to analyze the making of land deed by the Subdistrict Head in his position and function as Temporary PPAT in Bulakamba District, Brebes Regency, as well as to find out the legal consequences if an error occurred in its implementation.This research is a juridical-empirical approach. Data analysis techniques used qualitative data analysis. The juridical approach was based on a normative approach that analyzed various laws and regulations in the land sector, while the empirical approach is used to analyze normative laws.The results showed that, the temporary PPAT are more likely to only make a sale and purchase deed, because the Subdistrict Head itself is less active, due to busyness with government affairs in his area. The Subdistrict Head, as Temporary PPAT, has not yet installed the nameplate (Article 20 paragraph 2) PP No. 24 year 2016. The delay in submitting the deed and the documents in the land registration process conducted by the temporary PPAT Sub-District Head does not result in the cancellation of the deed that has been made.Suggestions to the Land Office in Brebes Regency is, they should work together with the PPAT Association (IPAT) and must routinely conduct guidance and supervision of the Land Deed Officials (PPAT), especially temporary PPAT in order to minimize mistakes.Keywords: Subdistrict Head, Temporary PPAT, Land Deed